A new model of third generation artificial turf degradation, maintenance interventions and benefits - Fleming, P. R.; Watts, C.; Forrester, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
High performing and safe outdoor third generation (3G) artificial turf (AT) fields demand high quality initial design and construction coupled with a comprehensive maintenance aftercare regime. However, in many cases maintenance of AT fields suffers from either a low-cost inexpert approach, or a one-size-fits-all generic approach based on general guidance with little to no evidence of effectiveness. Little previous research has addressed fundamental questions regarding how 3G AT systems degrade or have provided evidence of the effectiveness of maintenance interventions. Maintenance techniques currently utilised can be grouped into four separate categories (grooming, cleaning, decompaction and infill top-ups). The maintenance tools and processes for each category have been developed empirically through experience, mainly in response to qualitative observations with little quantitative evidence. This paper reports on a unique body of quantitative evidence of specific effects of maintenance interventions, on third generation AT surfaces (3G), collected over the past several years in collaboration with a major UK sports surface maintenance contractor. In addition, the data contributes new and robust evidence of the rate at which 3G surfaces can `lose` quantities of performance infill corroborated by the rate at which fields were topped up to maintain appropriate infill depths. A new quantified pitch degradation and maintenance benefits model is presented explaining 3G AT system degradation factors and mechanisms, their links to changes in system performance and the magnitudes of change effected by specific maintenance techniques. The new model is of direct benefit to both researchers and practitioners impacting on future best practice for assessing and maintaining the safety and performance of 3G AT.